Law, technology and society reimagining the regulatory environment - Brownsword, Roger (Law, science and society, 2019)
This book considers the implications of the regulatory burden being borne increasingly by technological management rather than by rules of law. If crime is controlled, if human health and safety are secured, if the environment is protected, not by rules but by measures of technological management--designed into products, processes, places and so on--what should we make of this transformation? In an era of smart regulatory technologies, how should we understand the 'regulatory environment', and the 'complexion' of its regulatory signals? How does technological management sit with the Rule of Law and with the traditional ideals of legality, legal coherence, and respect for liberty, human rights and human dignity? What is the future for the rules of criminal law, torts and contract law--are they likely to be rendered redundant? How are human informational interests to be specified and protected? Can traditional rules of law survive not only the emergent use of technological management but also a risk management mentality that pervades the collective engagement with new technologies? Even if technological management is effective, is it acceptable? Are we ready for rule by technology? Undertaking a radical examination of the disruptive effects of technology on the law and the legal mind-set, Roger Brownsword calls for a triple act of re-imagination: first, re-imagining legal rules as one element of a larger regulatory environment of which technological management is also a part; secondly, re-imagining the Rule of Law as a constraint on the arbitrary exercise of power (whether exercised through rules or through technological measures); and, thirdly, re-imagining the future of traditional rules of criminal law, tort law, and contract law